Microorganisms associated with Agos-os - Tan, Julie D.; Banaay, Charina Gracia B.; Parungao, Marilen M.; Cantera, Marie Antonette Ruth G. (2007)
The aerobic and anaerobic microflora of agos-os, a fermented sweet potato and meat mixture, were isolated, characterized and identified up to the genus level. Fermentation and isolation were done at the Visayas State University while characterization and identification were done at the University of the Philippines Los Baños. Various types of microorganisms, belonging to 10 different genera, were isolated from agos-os after fermentation. The bacteria belonged to the species Enterococcus, Corynebacterium, Acinetobacter, Escherichia and Klebsiella spp. while the molds belonged to the species Aspergillus, Mortierella and Phanerochaete. The yeast isolates belonged to the genera Candida and Torulopsis. Toward the end of the fermentation period when the pH had dropped to 4.03, bacteriocin-producing lactic acid bacteria {Enterococcus sp.) started to increase progressively.
Keywords: Meat; Microorganisms